Green biosynthesis of silver nanoparticles using ‘Polygonum hydropiper’ and study its catalytic degradation of methylene blue - Bonnia, Noor Najmi; Kamaruddin, Mohd Shahril; Nawawi, M. H.; Ratim, Suzana; Hassan, Noor Azlina; Ali, E. S. (Elsevier, 2016)
The green synthesis of silver nanoparticles with the small size and high stability paved the way to improve and protect the environment by decreasing the use of toxic chemicals and eliminating biological risks in biomedical applications. Plant mediated synthesis of silver nanoparticles is gaining more importance owing its simplicity, rapid rate of synthesis of nanoparticles and eco-friendliness. In this study, focus on biosynthesis of silver nanoparticles using Polygonum hydropiper extract and its catalytic degradation of hazardous dye, methylene blue has been highlighted. The rapid reduction of silver (Ag) ions was monitored using UV-Visible spectrophotometer and showed formation of silver nanoparticles within less than one hour with maximum absorption of silver nanoparticles at 430 nm. The major functional groups present in the synthesis responsible for the formation of silver nanoparticles. It was identified by using Fourier Transform Infrared spectrophotometer (FTIR). Field Electron Scanning Microscope (FESEM) was used to characterise the nanoparticles synthesized using P.hydropiper. The morphology of silver nanoparticles was predominantly spherical and aggregated into irregular structure with average diameter of 60 nm. In addition, this report emphasizes the effect of the silver nanoparticles on the degradation rate of hazardous dyes by sodium borohydride (NaBH4). The efficiency of silver nanoparticles as a promising candidate for the catalysis of organic dyes by NaBH4 through the electron transfer process is established in the present study.